The Social Media in Language Learning: Implications for Second Language Motivation and Linguistic Acquisition: a Comprehensive Review - zanyar ghafar (MultiTech Publisher, 2023)
This study provides a comprehensive analysis of the effects of social media on language acquisition, with a particular focus on the use of social media as instruments for developing language skills and as venues for intercultural dialogue. The first aspect under consideration is to the possible impact of social media as instruments for developing language skills, including reading and writing, as well as listening and speaking abilities. The first examines the role of social media as cross-cultural interaction channels in enhancing pragmatic socioeconomic skills and second language (L2) motivation, while the latter specifically investigates the potential implications of social media on these aspects. The findings suggest that social media offers several advantages and serves various purposes in the language learning processes. These include the availability of genuine input materials, the provision of less anxiety-inducing practice environments, a plethora of chances for intercultural dialogue, and the promotion of learner cooperation. The research further underscores possible limits associated with social networking platforms, such as issues over distraction and contradicting information. Finally, several potential avenues for further empirical investigation have been suggested.